Influence of tidal dissipation on outcomes of binary–single encounters between stars and black holes in stellar clusters. Issue 2 (3rd October 2022) - Hellström, Lucas; Askar, Abbas; Trani, Alessandro A; Giersz, Mirek; Church, Ross P; Samsing, Johan
ABSTRACT: In the cores of dense stellar clusters, close gravitational encounters between binary and single stars can frequently occur. Using the tsunami code, we computed the outcome of a large number of binary–single interactions involving two black holes (BHs) and a star to check how the inclusion of orbital energy losses due to tidal dissipation can change the outcome of these chaotic interactions. Each interaction was first simulated without any dissipative processes and then we systematically added orbital energy losses due to gravitational wave emission [using post-Newtonian (PN) corrections] and dynamical tides and recomputed the interactions. We find that the inclusion of tides increases the number of BH–star mergers by up to 75 per cent; however, it does not affect the number of BH–BH mergers. These results highlight the importance of including orbital energy dissipation due to dynamical tides during few-body encounters and evolution of close binary systems within stellar cluster simulations. Consistent with previous studies, we find that the inclusion of PN terms increases the number of BH–BH mergers during binary–single encounters. However, BH–star mergers are largely unaffected by the inclusion of these terms.